Predicting religion - Keen, Daniel E. Rossi (The journal for cultural and religious theory, 2004)
A profile of Predicting Religion: Christian, Secular and Alternative Futures. Edited by Grace Davie, Paul Heelas, and Linda Woodhead. Burlington: Ashgate Publishing Company, 2003 pp. xii + 253. $29.95 (paper). ISBN 0-7546-3010-2.